Characterization of Calflagin, a Flagellar Calcium-Binding Protein from Trypanosoma congolense. - Brett A Eyford; Laura Kaufman; Orly Salama-Alber; Bianca Loveless; Matthew E Pope; Robert D Burke; Enock Matovu; Martin J Boulanger; Terry W Pearson (Public Library of Science (PLoS), 2016)
BACKGROUND:Identification of species-specific trypanosome molecules is important for laboratory- and field-based research into epidemiology and disease diagnosis. Although Trypanosoma congolense is the most important trypanosome pathogen of cattle in Africa, no species-specific molecules found in infective bloodstream forms (BSF) of the parasites have been identified, thus limiting development of diagnostic tests. METHODS:Immuno-mass spectrometric methods were used to identify a protein that is recognized by a T. congolense-specific monoclonal antibody (mAb) Tc6/42.6.4. The identified molecule was expressed as a recombinant protein in E. coli and was tested in several immunoassays for its ability to interact with the mAb. The three dimensional structure of the protein was modeled and compared to crystal- and NMR-structures of the homologous proteins from T. cruzi and T. brucei respectively, in order to examine structural differences leading to the different immunoreactivity of the T. congolense molecule. Enzyme-linked immunosorbent assays (ELISA) were used to measure antibodies produced by trypanosome-infected African cattle in order to assess the potential for use of T. congolense calflagin in a serodiagnostic assay. RESULTS:The antigen recognized by the T. congolense-specific mAb Tc6/42.6.4 was identified as a flagellar calcium-binding protein, calflagin. The recombinant molecule showed immunoreactivity with the T. congolense-specific mAb confirming that it is the cognate antigen. Immunofluorescence experiments revealed that Ca2+ modulated the localization of the calflagin molecule in trypanosomes. Structural modelling and comparison with calflagin homologues from other trypanosomatids revealed four non-conserved regions on the surface of the T. congolense molecule that due to differences in surface chemistry and structural topography may form species-specific epitopes. ELISAs using the recombinant calflagin as antigen to detect antibodies in trypanosome-infected cattle showed that the majority of cattle had antibody responses. Area under the Receiver-Operating Characteristic (ROC) curves, associated with host IgG and IgM, were calculated to be 0.623 and 0.709 respectively, indicating a positive correlation between trypanosome infection and the presence of anti-calflagin antibodies. CONCLUSIONS:While calflagin is conserved among different species of African trypanosomes, our results show that T. congolense calflagin possesses unique epitopes that differentiate this protein from homologues in other trypanosome species. MAb Tc6/42.6.4 has clear utility as a laboratory tool for identifying T. congolense. T. congolense calflagin has potential as a serodiagnostic antigen and should be explored further for its utility in antigen-detection assays for diagnosis of cattle infections.